Combining infusion warmer and automatic infusion pressure bag to stabilize blood pressure and body temperature in caesarean section - Brilianti Chrisnajayantie Raden Roro; Dina Indrati Dyah Sulistyowati; Suharsono Suharsono; Raden Rara Sri Endang Pujiastuti; Lucia Endang Hartati (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Patients undergoing caesarean section (CS) with spinal anaesthesia are at risk of hypotension and hypothermia due to peripheral vasodilation and decreased venous return. These conditions may be exacerbated by the administration of room-temperature intravenous fluids (21–23°C) and manual pressure infusion. Using a fluid warmer can help prevent hypothermia, while an automatic infusion pressure bag can accelerate fluid delivery, potentially maintaining blood pressure and body temperature stability. However, these interventions have not yet been studied as a combined approach. Purpose: To evaluate the effect of using a fluid warmer in combination with an automatic infusion pressure bag on blood pressure and body temperature in patients undergoing caesarean section. Method: This quasi-experimental study used a pre-test and post-test with control group design and included 64 patients undergoing CS, divided into intervention and control groups. The intervention group received warmed fluids (37–39°C) administered through an automatic infusion pressure bag from the sign-in phase until discharge from the recovery room. Measurements were taken at four time points: preoperatively during sign-in, intraoperatively at 15 and 30 minutes after anaesthesia induction, and postoperatively 15 minutes in the recovery room. Results: There was no statistically significant difference in blood pressure between groups (p > 0.05), although a small clinical effect was observed (ηp² = 0.01–0.06). Body temperature showed statistically and clinically significant differences at all measurement points (p < 0.05, ηp² > 0.14), indicating a strong effect of the intervention. Conclusion: The use of a fluid warmer combined with an automatic infusion pressure bag is clinically effective in maintaining blood pressure stability and statistically and clinically effective in stabilizing body temperature during caesarean section procedures.